Resolution Effort of Electricity Theft Crimes at PLN UP3 Sorong - Saiful HMH; Dwi Pratiwi Markus; Muh Akhdharisa SJ; Mohammad Belayet (JUSTISI, 2024)
This study aims to investigate the impact of electricity theft on PLN and the state and analyze the out-of-court resolution system for electricity theft by PT PLN UP3 Sorong Branch. The method used is an empirical juridical approach focusing on case analysis and field data. The results showed that PLN uses the additional bill, Tagihan Susulan (TS) as the fine, as an out-of-court resolution for electricity theft cases. However, there is an option to settle through the court if the customer objects. Although the number of cases is decreasing, challenges in addressing the problem of electricity theft still exist, and its resolution requires a holistic approach that considers the principles of justice and applicable law. In conclusion, electricity theft violates the law that must be addressed effectively to maintain the sustainability of the electricity sector and justice for all parties involved.